Deteksi Ustilago scitaminea Pada Tebu Dengan Antibodi Monoklonal = Detection o/Ustilago scitaminea on Sugarcane by Monoclonal Antibody - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Abstract Monoclonal antibodies were produced against mycelia and extra cellular proteins of Ustilago scitaminea and used for detection of infected sugarcane collected from Pengasih and Prambanan. Fractionation of mycelia and culture filtrat proteins were done with ammonium sulphate 85% and ultracentrifugation, were identified with the SDS-PAGE. The results indicated that mycelia and culture filtrat proteins of U. scitaminea had 50-141.435 kDa molecular weight. Four monoclonal antibodies: 26E4, 34G8,34G,, and 45C4 were specific for infected plants. The 26E4 was belong to IgM class of immunoglobulin, but the others was belonging IgG. All four monoclonal antibodies recognised U. scitaminea in the infected plants.